A Study of English Language Needs for Nursing Students at Stikes Intan Martapura - Rizkyka, Adetya Nor; Rizkina, Amalia (Universitas Achmad Yani, 2025)
English is commonly offered as a general subject in universities for students outside the English major, such as those in the Nursing Department at STIKes Intan Martapura. However, it would be more effective if the material were adapted to suit the specific discipline, a practice known as English for Specific Purposes (ESP). Understanding the perspectives of different stakeholders is crucial to determine the significance of English in a nursing career and to identify the most suitable content. This study aimed to explore the English language needs of Nursing students at STIKes Intan Martapura, focusing on ESP materials. The research employed a questionnaire as the primary tool for data collection. Participants included sixth-semester Nursing students from the academic year 2024/2025, with a total population of 90 students divided into three classes. From this number, 20% were selected as samples, resulting in 18 students participating across the classes. The findings reveal that students recognize the vital role of English in the Nursing field. Although English instruction currently follows a general curriculum, students expressed a strong desire for materials more closely aligned with their practical duties and professional demands. The results are expected to assist ESP instructors and other related parties in designing more relevant and practical English programs for Nursing students.